Synthesis and Characterization of Hydroxyapatite (HAp) from Eggshell Waste for Biomedical Applications - Zahlan Arief, Nur Nadhirah Hani; R. Zaiedy, Mohamad Naufal Muzammil; Zubairi, Puteri Nur Hannani; ROSLEY, ROZAINITA (Multidisciplinary Applied Research and Innovation, 2025)
Approximately 250,000 tons of eggshell waste are generated annually. This study proposes a sustainable and economically viable solution by repurposing this waste into valuable biomaterials like hydroxyapatite (HAp). HAp was successfully synthesized from eggshell waste through a two-step process involving calcination and chemical precipitation. The eggshells were initially calcined at temperatures ranging from 700°C to 1100°C with 100°C intervals to convert calcium carbonate (CaCO₃) into calcium oxide (CaO). The calcined powder was then mixed with distilled water and phosphoric acid before undergoing a 24-hour aging process. The resulting precipitates were centrifuged and re-calcined at 800°C. Characterization of the synthesized HAp was conducted using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM/EDX). XRD analysis confirmed the formation of HAp through the successful conversion of CaCO₃ to CaO. FTIR spectra indicated the presence of phosphate (PO₄³⁻), carbonate (CO₃²⁻), and hydroxyl (OH⁻) groups, further confirming the synthesis of HAp. SEM analysis revealed an increase in HAp particle size with rising calcination temperatures. Additionally, EDX analysis of the 700°C sample showed a Ca/P ratio of 1.67, which matches the stoichiometric ratio of HAp.